Effects of resisted exercise in post-covid-19 patients (Research, Society and Development, 2022)
Objective: To map the scientific evidence on the importance of resistance exercise in the rehabilitation of people affected by Covid-19. Methods: This is a scoping review carried out in November 2022 and based on the following research question: “What is the existing scientific evidence that deals with the importance of resistance training in the rehabilitation of people affected by Covid-19”. Articles retrieved by combining the terms “resistance exercise”, “Covid-19”, “resistance training” and “physical exercise” on the Google Scholar platform were analyzed, in addition to searches on websites and repositories. The analysis of the four articles that made up the sample of this study was descriptive. Results: Resistance training, at light and moderate intensities, has an immunomodulatory action by helping in the production of several cellular and hormonal markers, in addition to contributing to the reduction of inflammation. Conclusion: The practice of resistance exercise has been shown to be essential both to prevent and rehabilitate people who have been contaminated by SARS-CoV-2, acting in a unique way in immune modulation.